Peran Orangtua dalam Mendampingi Pembelajaran Siswa Pada Masa Pandemi Covid-19 - Nurfadlilah Muhyi (Jurnal Syntax Transformation, 2021)
The role of parents is needed in the learning process of students while studying from home, the role of parents is very much needed, especially in accompanying student learning. Because the need for more attention from parents to direct children in learning. Due to the current pandemic, students cannot study at school with teachers as usual. This study was to determine the role of parents in assisting student learning during the COVID-19 pandemic at SDN Kwaron 2. By using phenomenological qualitative research methods, the data obtained were using observation, interview, and documentation. For data analysis techniques using: data reduction, data display, data verification. To check the validity of the data by: (1) credibility: a. participation extension, b. persistence of observation, c. triangulation, (2) transferability, (3) dependability, (4) confirmability. The results of this study are parents can assist students' learning at home properly and are adjusted to the busyness of parents to develop and succeed in student education